Esthetic-functional reconstruction of posterior teeth with direct restorations (a case report) - A. V. Mitronin; D. A. Ostanina; E. A. Ismaylov (LLC "Endo Press", 2021)
Teeth restoration in respect with anatomy and function with direct composite restoration does not lose its relevance for many years. The driving factor for the widespread use of direct restorations is satisfactory aesthetic results, simplicity and high speed of their implementation, and relatively low cost. Moreover, dental restorations in direct technique are constantly being improved due to the unprecedented growth of technologies in the production of dental materials and equipment, which are now living their golden age. This article presents a clinical case of replacing old incompetent fillings with impaired marginal fit of the posterior teeth with highly aesthetic and functional composite restorations.